Cash holdings, the internal capital market, and capital allocation efficiency in listed companies. Issue 1 (31st December 2023) - Zhao, Jiahua; Wang, Minglin; He, Qiuqin
Abstract: The rise in firm-level cash asset ratios has become a prominent trend in countries around the world which may further influence the capital allocation efficiency. This study analysed the inefficient effect of cash holdings on the capital allocation by combining the internal capital market theory with principal–agent theory and asymmetric information theory. The theoretical hypotheses were tested using linear panel regression models based on financial data from Chinese listed enterprises. We found that corporations holding more cash assets had lower capital allocation efficiency than those with fewer cash assets, which is consistent with agency theory and asymmetric information theory. Internal capital markets exacerbated this adverse effect. Additional testing was conducted to examine the heterogeneity of this effect between different types of ownership and strategy; the findings showed that an increase in cash holdings had a greater marginal impact on overinvestment among privately owned enterprises and underinvestment among state-owned enterprises. Internal capital market operation alleviated the problem of overinvestment but exacerbated the problem of underinvestment in privately owned enterprises, whereas it increased overinvestment in state-owned enterprises. The results suggested that different types of enterprises should deal with the inefficient effect of cash assets based on the causes of inefficient investment.